Efficacy of mesenchymal stem cell-based therapies in the treatment of perianal fistulizing Crohn’s disease: a systematic review and meta-analysis - Lucas Guillo; Robinson Gravier Dumonceau; Mélanie Vélier; Mélanie Serrero; Fanny Grimaud; Florence Sabatier; Jérémy Magalon (Stem Cell Research & Therapy)
Abstract Background Perianal lesions of Crohn’s disease (CD) are complex and disabling conditions. Mesenchymal stem cell (MSC)-based therapies have emerged as an innovative approach in managing refractory perianal fistulizing CD. We conducted a systematic review and meta-analysis to describe and compare combined remission and clinical outcomes of MSC-based therapies, and then whether one approach stands out from the rest. Methods We searched in MEDLINE, EMBASE and CENTRAL (up to December 31, 2023) all prospective studies assessing a local injection of MSC-based therapy in perianal fistulas of CD. The primary outcome was achievement of combined remission. MSC-based therapy strategies were compared. Results Twenty-five studies were included in the meta-analysis, enrolling 596 patients with perianal fistulizing CD. The combined remission rate at 3, 6 and 12 months were 36.2% (95% confidence interval (CI), 24.5–49.7), 57.9% (95% CI 51.3–64.2) and 52% (95% CI 38.8–64.8), respectively. MSC-based therapies demonstrated a significant effect in achieving combined remission compared to placebo at 3 months (relative risk (RR) = 1.6; 95% CI 1.0–2.8) and at 6 months (RR = 1.5; 95% CI 1.1–1.9). At 6 months, the combined remission rate was 57.2% (95% CI 47.2–66.6) for adipose-derived stem cells (ASCs) and 55.7% (95% CI 26.4–81.5) for bone marrow-derived stem cells (BMSCs). In the network meta-analysis, allogeneic ASCs and BMSCs did not demonstrate superiority over each other (RR = 0.74; 95% CI 0.31–1.77). Conclusion MSC-based therapies are effective for achieving combined remission of refractory and/or complex perianal fistulizing CD. The optimal efficacy effect is reached after 6 months of treatment. No superiority has yet been demonstrated between ASCs and BMSCs therapies